Jiu-Jitsu-Specific Performance Test: Reliability analysis and construct validity in competitive athletes - da Silva Junior, J. N.; Kons, R. L.; de Lucas, R. D.; Detanico, D. (The Journal of Strength and Conditioning Research, 2022)
The aim of this study was twofold: to analyze the test-retest reliability and sensitivity of Jiu-Jitsu "anaerobic" performance test (JJAPT) variables, and to determine the construct validity of JJAPT by comparing groups of athletes with different levels and technical profiles. Sixty Brazilian Jiu-Jitsu (BJJ) athletes participated in this study. The reliability analysis was performed with all athletes and the construct validity was tested in the group comparisons—novice vs. advanced level and guard versus pass fighters. From the JJAPT, the number of repetitions, rate of perceived exertion (RPE) and average heart rate were assessed over the 5 sets. The test-retest reliability was assessed by absolute and relative analysis for each variable. The construct validity was tested by comparison means and the receiving operator characteristic (ROC) curve was used with the level of significance set at 5%. The main results demonstrated excellent test-retest reliability for all but the RPE in the first sets, with good sensitivity and agreement. The maximal number of repetitions in the JJAPT showed good construct validity, as it showed sensitivity to discriminate the performance between the advanced and novice BJJ athletes (p < 0.001, ROC curve area of 0.95). However, no significant difference was found between the technical profile groups (p > 0.05). We concluded that the JJAPT presents excellent performance reliability as a specific-sport test. In addition, the test presented evidence of construct validity, because it discriminated the performance between the advanced and novice BJJ athletes.